AOZORA: long-term safety and joint health in paediatric persons with haemophilia A without factor VIII inhibitors receiving emicizumab – protocol for a multicentre, open-label, phase IV clinical study - Seitaro Yoshida; Masashi Taki; Hideyuki Takedani; Midori Shima; Keiji Nogami; Azusa Nagao; Haruko Yamaguchi-Suita; Yui Kyogoku; Akira Ishiguro; Kaoru Kitsukawa (BMJ Open)
Introduction Persons with haemophilia A (PwHA) commonly experience regular bleeding into joints, which may result in joint damage and complications such as degenerative arthritis. Emicizumab has previously demonstrated efficacy in reducing the occurrence of joint bleeds and target joints, along with having a favourable safety profile; however, data on the long-term effects on joint health are lacking. The AOZORA study will evaluate the long-term safety and joint health of paediatric PwHA without factor (F)VIII inhibitors taking emicizumab; here, we report the details of the study protocol and baseline data.Methods and analysis AOZORA is a multicentre, open-label, phase IV clinical study in Japan that aims to enrol approximately 30 PwHA aged <12 years without FVIII inhibitors. The primary endpoints include a long-term safety evaluation of adverse events, laboratory test abnormalities and FVIII inhibitor development; and a long-term joint health assessment using MRI and the Hemophilia Joint Health Score. Exploratory endpoints include characterising participants’ physical activities and the number of activity-related bleeds requiring coagulation factor treatment. Currently, 30 participants have been enrolled, including 20 emicizumab-naïve participants and 10 who transferred from HOHOEMI, a previous study in paediatric PwHA.Ethics and dissemination The AOZORA study was approved by the Institutional Review Boards of Nara Medical University and the St Marianna University Group. The study will be conducted in compliance with the Declaration of Helsinki, the standards stipulated in paragraph 3 of Article 14 and Article 80-2 of the Pharmaceuticals, Medical Devices and Other Therapeutic Products Act, the Ministerial Ordinance on Good Clinical Practice and the Ministerial Ordinance on Good Post-marketing Study Practice. Data will be published in peer-reviewed journals and presented at Global congresses.Trial registration number JapicCTI-194701.